BAHAYA ARTIFICIAL INTELLIGENCE BAGI VALIDITAS EVALUASI DALAM PENYELESAIAN TUGAS AKADEMIK MAHASISWA - Aisyah; Fathurrahman Muhtar; Suhirman; Abdul Fattah; Ismail Thoib (Walada: Journal of Primary Education, 2026)
The digitalization of education has driven the massive integration of Artificial Intelligence (AI) in higher education. However, the uncontrolled use of AI raises concerns regarding the authenticity of learning assessments, particularly among Islamic Education (PAI) students at UIN Mataram. This study aims to examine the impact of AI usage on the validity of assessments and the degradation of academic integrity. This research employs a descriptive qualitative approach. Data were collected through in-depth interviews with PAI students from the 2023 and 2024 cohorts, field observations, and documentation, and were analyzed using the interactive model of Miles and Huberman. The findings indicate that the dominance of AI triggers cognitive erosion, reflected in declining literacy, critical thinking skills, and originality of ideas due to dependence on instant answers. This “shortcut” phenomenon undermines the principles of shiddiq (honesty) and amanah (responsibility), resulting in academic scores that no longer validly represent students’ actual intellectual capacities. Therefore, it is necessary to reconstruct evaluation methods and establish strict ethical guidelines for AI usage within the PAI program to preserve academic integrity and the moral quality of graduates.